Comparative evaluation of amisulpride and escitalopram on Hamilton anxiety rating scale among depression patients in a tertiary care teaching hospital in Nepal - Kaul, Vijay; Dutta, Shakti B.; Beg, Mirza A.; Bawa, Shalu; Anjoom, Mohammed; Singh, Nand K.; Dutta, Srihari (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Depression is an important global public health problem and is a major cause of disability and premature death. The present study was conducted to compare efficacy and safety of amisulpride and escitalopram on Hamilton anxiety rating scale (HAM-A) among depression patients in a tertiary care teaching hospital in Nepal. Methods: The study was conducted in patients for 1-year in the Department of Neuropsychiatry, Nepalgunj Medical College and Teaching Hospital. A total of 117 depression patients were divided into two groups. Group I (58 patients) received amisulpride tablet at a dose of 50 mg/day and Group II (59 patients) were given escitalopram at a dose of 10 mg/day. The patients were required to follow-up at 4, 8 and 15 weeks. The efficacy of the drugs was calculated by HAM-A. Adverse drug reactions (ADRs) were monitored at every follow-up. Appropriate statistical tools using Graphpad instat 3.0 were used for analysis p<0.05 was considered significant. Results: HAM-A score in group receiving amisulpride at 0 and 15 weeks was 19.83±0.33 and 8.17±0.32 (p<0.0001). HAM-A score in group receiving escitalopram at 0 and 15 weeks was 20.76±0.28 and 8.98±0.24 (p<0.0001). Gastrointestinal disturbances, sexual disturbances, amenorrhea, lactation, agitation, and insomnia were the commonly encountered ADRs. Conclusion: Both amisulpride and escitalopram were highly effective in the treatment of anxiety in depression patients during the study period. Further, more clinical studies with longer follow-up duration are needed to substantiate the therapeutic effects of amisulpride.